2022
DOI: 10.1111/oik.09465
|View full text |Cite
|
Sign up to set email alerts
|

Are fine roots ‘leaves underground' in terms of allometry? A test in a tropical forest successional series in southwest China

Abstract: Fine roots have been hypothesized to be ‘leaves underground' in terms of vascular network, but this hypothesis has rarely been tested within the framework of metabolic scaling theory (MST). We measured average fine‐root (diameter < 1 mm) mass (M), surface area (A), volume (V), diameter (D) and length (L) for 216 soil cores from 24 plots across four successional stages in tropical forests of Xishuangbanna (southwest China), and examined eight scaling relationships between these variables at the individual root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Reference in this Special Issue Temperate Alonso-Crespo et al 2023, Klimešová and Herben 2023, Mafa-Attoye et al 2023, Mao et al 2023, Schuster et al 2023, Slette et al 2023, Yang et al 2023(Sub)Tropical Dallstream et al 2023, Dai et al 2023,Gagliardi et al 2023, Guo et al 2023, Leroy et al 2023, Kotowska et al 2023 a large variety of fine-root systems coexist in hyper-diverse tropical plant communities. Besides adding information from underexplored biomes, this Special Issue further highlights the importance of incorporating additional traits covering all belowground trait categories (McCormack et al 2017) -albeit to different extents -in the context of a RES (Table 1).…”
Section: Climate Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference in this Special Issue Temperate Alonso-Crespo et al 2023, Klimešová and Herben 2023, Mafa-Attoye et al 2023, Mao et al 2023, Schuster et al 2023, Slette et al 2023, Yang et al 2023(Sub)Tropical Dallstream et al 2023, Dai et al 2023,Gagliardi et al 2023, Guo et al 2023, Leroy et al 2023, Kotowska et al 2023 a large variety of fine-root systems coexist in hyper-diverse tropical plant communities. Besides adding information from underexplored biomes, this Special Issue further highlights the importance of incorporating additional traits covering all belowground trait categories (McCormack et al 2017) -albeit to different extents -in the context of a RES (Table 1).…”
Section: Climate Regionmentioning
confidence: 99%
“…1). Guo et al (2023) further showed that allometric relationships (and thus covariations) among root traits also changed as a function of tree size in a tropical forest community. The position of species within the RES may thus change with time (at least, along the collaboration axis), but whether these shifts indeed reflect changes in the degree of mycorrhizal dependency is still controversial (Leroy et al 2023).…”
Section: Intraspecific Patterns In Root Trait Variation: Insights Tow...mentioning
confidence: 99%
“…2a). However, Guo et al (2022) found that multiple scaling relationships between fine-root area, volume, diameter and mass all conform to MST's predictions for tree woody organs instead of leaves. Their results and ours are not exclusive because they examined allometries among traits related to root morphology, while we examined the FRP-FRB allometry concerning root productivity.…”
Section: Allometric Relationship Between Fine-root Biomass and Produc...mentioning
confidence: 66%
“…Their results and ours are not exclusive because they examined allometries among traits related to root morphology, while we examined the FRP-FRB allometry concerning root productivity. Fine roots have important structural differences from leaves, including a key difference that leaves are nearly two-dimensional while fine roots are three-dimensional objects similar to woody organs (Price and Enquist 2007), which can lead to markedly difference in morphological allometries (Guo et al 2022). Thus, our results, together with Guo et al (2022), suggest that fine roots may be "leaves underground" in terms of productivity-related allometries, but differ from leaves for morphology-related allometries.…”
Section: Allometric Relationship Between Fine-root Biomass and Produc...mentioning
confidence: 67%
See 1 more Smart Citation